(untitled) (Journal of the Bangladesh Agricultural University, 2017)
Stevia represents an interesting species for the development of new ingredients characterized by a low caloric contribution having high antioxidant and phytochemical properties. As a valuable organic fertilizer, poultry manure (PM) serves as a suitable alternate to chemical fertilizer due to having higher total solid content than most other manures. The present study was conducted in the net house of the Department of Agricultural Chemistry, BangladeshAgriculturalUniversity, Mymensingh to evaluate the effects of poultry manure on growth and leaf yield of stevia and post-harvest soil fertility. The experiment was laid out in a Complete Randomized Design (CRD) with three replications. PM was applied at rates of 0, 5, 7.5 and 10 t ha−1. Data of the plant height, number of branches and number of leaves per plant were collected at 0, 15, 30, 45 and 60 days after planting (DAP). At harvest, leaf area, fresh weight, dry weight of leaves of stevia and post-harvest soil were evaluated. Plant that received 5 t ha−1 of PM was the best with respect to all the parameters assessed except post-harvest soil fertility. The contents of total N, available P, exchangeable K, Ca, Mg, available S, Zn and B were significantly increased with the increased levels of PM up to 10 t ha−1 in both soils. pH and soil organic matter content were also increased several folds and favored higher growth and yield of stevia. It can be recommended from the findings of the study that farmers should apply PM @ 5 t ha−1 to obtain maximum growth and leaf yield of stevia where as PM @ 10 t ha−1 can be applied for maintaining soil fertility in the agro-climatic condition of Bangladesh. J. Bangladesh Agril. Univ. 15(2): 212-218, December 2017